THE RELATIONSHIP BETWEEN SELF-CONTROL AND EGOCENTRIC ATTITUDE IN CLASS XI STUDENTS OF REIS CENDIKIA MEDAN VOCATIONAL SCHOOL ACADEMIC YEAR 2021-2022 - Dinda Rizka; Ika Sandra Dewi; Nur Asyah (Yayasan Citra Dharma Cindekia, 2021)
This study aims to: (1) determine the self-control of class XI students of SMK Reis Cendikia Medan in the 2021/2022 academic year. (2) to find out the egocentric attitude of class XI students of SMK Reis Cendikia Medan in the 2021/2022 academic year. (3) to find out whether there is a significant relationship between self-control and egocentric attitudes of class XI students at SMK Reis Cendikia Medan in the 2021/2022 academic year. The population in this study were students of class XI SMK Reis Cendikia Medan for the academic year 2021/2022, totaling 120 students were taken. As a sample of 30 students, the sample was taken using a random sampling technique, namely a sample taken in such a way that each research unit or unit element of population has an equal chance of being selected as a sample. The data of this study were collected using a questionnaire, namely a questionnaire about self-control and egocentric attitude. The form of the questionnaire used is a multiple choice form with 40 items for self-control variable (X) and 40 items for egocentric attitude (Y) which were first tested and analyzed to obtain a valid and reliable questionnaire. The correlation test technique used is the product moment correlation formula. From the calculation results, the correlation coefficient between self-control (X) and egocentric attitude (Y) is 0.740 and 0.430, according to the interpretation of the product moment correlation index, the figure indicates a strong or high relationship. . The results of the hypothesis test state that there is a significant relationship between self-control and the egocentric attitude of XI students of SMK Reis Cendikia Medan in the 2019/2020 academic year at a significant level of 5%. (tcount > ttable : 0.740 and 0.430 > 0.374)